SISCAL: Control of activities for the satisfaction of quality of customer service Electro Sur Este S.A.A. - Angelino Chancco, Evelin (2020)
The electricity company Electro Sur Este in the department of Apurímac has a program called Customer Service Quality Satisfaction Index (ISCAL), whose purpose is to carry out social responsibility activities towards its customers and the population, it does not have a mechanism to control and organize the information of the different activities; Therefore, a web application was developed in C # programming language, TypeScript, JavaScript Sql Server and the cloud installation environment under XP methodology. The pre-experimental design, hypothetical deductive method, having as results that "SISCAL" globally improved the control of activities by 70% with a sample of 4036 activities. And the evaluation of usability and functionality is at the good level.